Tests of efficacy of antidotes for removal of methylmercury in human poisoning during the Iraq outbreak - Clarkson, T W; Magos, L; Cox, C; Greenwood, M R; Amin-Zaki, L; Majeed, M A; Al-Damluji, S F (The Journal of pharmacology and experimental therapeutics, 1981)
Three complexing agents and a thiolated resin were tested for their ability to reduce the T 1/2 of methylmercury in blood during an outbreak of human poisoning. The slope of the line relating the natural logarithm of the blood concentration to time during treatment was calculated by a parametric (linear regression) and a nonparametric (two-point) method. The mean slope for each treatment group was calculated and the T 1/2 was calculated from the mean slope. Both the linear regression and two-point methods yield similar mean values. The "two-point" T 1/2 will be quoted here. The mean T 1/2 in six patients receiving no specific treatment was 65 days and in 10 patients receiving placebo was 61 days, and these values did not differ from those reported in the literature. All four treatments significantly reduced the mean T 1/2 values below the mean for the combined placebo and no treatment groups. Sodium 2,3-dimercaptopropane-1-sulfonate was the most effective agent, reducing the mean T 1/2 in 10 patients to 10 days. The thiolated resin given to eight patients produced a mean T 1/2 of 20 days. The penicillamines also produced a significant reduction in T 1/2 values; the mean T 1/2 for D-penicillamine in 12 patients was 26 days and N-acetyl-DL-penicillamine in 17 patients yielded a mean T 1/2 of 24 days. This is the first report of the effects of sodium 2,3-dimercaptopropane-1-sulfonate and resin in human subjects exposed to methylmercury. No adverse effects were observed in any of the treatment groups. A clinical trial was not possible but it is concluded that agents that reduce blood levels and accelerate excretion are probably clinically useful if given before irreversible damage has occurred.